Trastorno de ansiedad social y su influencia en el rendimiento académico de un estudiante de 15 años de edad de la Unidad Educativa Eneida Uquillas de Rojas ciudad de Babahoyo - Bravo Rizo, Maite Estefania (2020)
In the present Case Study with the topic of social anxiety disorder and its influence on the academic performance of a 15-year-old student from the Eneida Uquillas de Rojas Educational Unit in Babahoyo, problems in his academic performance are presented by the lack of development that is the result of social anxiety, so the objective is to determine how the TAS influences academic performance, using psychological tools such as clinical history, the Hamilton anxiety test, Inventory Test (SPIN) Social Anxiety , Social Phobia and Self-esteem, under the criteria indicated by the DSM-5, the diagnosis of this patient is social anxiety, and it is thus that an outline of the psychotherapeutic process based on cognitive-behavioral therapy could be carried out in order to modify these behaviors that cause anxiety and that leads to problems with their academic performance.